User Requirement Analysis on Sales Information System at PT. MITRA INDOLINK - Mochamad Naufal Akbar; Deddy Purba Pratama; Kevin Alexander; Suzanna Suzanna (Bina Nusantara University, 2024)
The era is developing very quickly and dynamically, creating many changes that result in tight competition in the business world. The business world needs to follow the progress of information systems. Analysis of user needs in the business world needs to be done in order to find out the various needs of the company. The purpose of this study is to find out the results of the analysis of user requirements that are needed and that can support sales operations in the sales information system of PT. Mitra Indolink Grosir supports the company's sales operations. The research method used is by interviewing users of the information system which is then processed using the System Usability Scale (SUS) technique. The results of the analysis show that the sales information system with the TikTok shop application can be used efficiently and meets user needs (user requirements) with a value of 69.65 which is included in grade C.